(untitled) (Education in the 21st Century, 2024)
In the early years of the Armenian community of Syria, we were fortunate to have educators with advanced pedagogical training or experience playing educational roles. They came from institutions such as the Berberian Central College of Constantinople, the Sanasarian College of Karin (Erzurum), the Armash Seminary near Constantinople and the Gevorgian Seminary of the Mother See Holy Etchmiadzin. However, as these educators in time became less available, it became clear that the community needed to seek out and support new educational professionals. Armenian communities in the Middle East, being near their historical homeland, have demonstrated a strong commitment to preserving their national identity, religion, language, historical memory, and culture. The presence of Armenian studies centers in these communities has been instrumental in comprehending and safeguarding the Armenian heritage. In 1938, the initiative to train pedagogical experts met with a positive response from the national authority and intellectuals of the Armenian community in Syria, leading to the establishment of the Aleppo Armenian Teachers’ Union. This union aimed to enhance the intellectual capabilities of educators, promote national education, foster public interest in national education and ensure the intellectual development of the new generation through the latest pedagogical practices. Nevertheless, one of the significant challenges confronted by the elementary schools in Syria was the inadequacy of methodical training for teachers due to the absence of Armenian studies centers for teacher training. This concern was only addressed in 1996 with the establishment of the Aleppo Armenian Studies Center by the Hamazkayin’s Syrian Regional Administration which sought to bridge this gap. The presence of proficient Armenian teachers has played a crucial role in the preservation and advancement of the Western Armenian language. Through their dedication, the Armenian generation has thrived and flourished both within and beyond the realms of educational institutions.